O Piruvato Melhora A Energética Mitocondrial Num Modelo Animal Ex-vivo de Isquemia Miocárdica Global - Monteiro, P (2003)
Pyruvate is an energy substrate with known cardioprotective activity. We know now that this is due not only to its antioxidant activity, but also to its reduction of intracellular acidosis, modulation of intracytosolic calcium and improvement of cardiomyocyte contractility. However, the role of cardiac mitochondria in such positive effects has only recently begun to be understood and the exact mechanisms of the effect of pyruvate on mitochondria are still largely unknown. Aiming to study the effect of pyruvate on cardiac mitochondrial function during acute ischemia, we used an ex-vivo animal model, perfused in a Langendorff system and then subjected to ischemia in the presence and absence of pyruvate. We evaluated the mitochondrial membrane electrical potential, the respiratory chain O2 consumption (and respiratory control ratio) and the energy charges generated with different energy substrates. We conclude that pyruvate has some effect on the mitochondrial oxidative system (by non-significantly improving the respiratory control ratio), but its main action is on the phosphorylation system, significantly decreasing the time taken to complete a phosphorylation cycle (lag phase) and improving ATP production (increase in energy charge), thus allowing better maintenance of mitochondrial membrane structure, with consequent improvement of the electrical potential after a phosphorylation cycle. These findings have enabled better understanding of the mechanisms behind pyruvate cytoprotection in ischemic cardiomyopathy, clearly highlighting the essential role of cardiac mitochondria in this process.